Sphingolipids related to apoptosis from the point of view of membrane structure and topology. (November 2001) - van Blitterswijk, W. J.; van der Luit, A. H.; Caan, W.; Verheij, M.; Borst, J.
Abstract : Sphingolipids and their metabolites are implicated in signal transduction, but the mechanisms are still poorly understood. In particular, the presumed function of ceramide as a second messenger remains controversial. Here, we emphasize the importance of both ceramide and sphingomyelin for membrane structure. The effects of sphingo-lipid turnover in the induction and effector phases of apoptosis are explained by their impact on membrane microdomains that are relevant for cell signalling or changes in morphology. The topology of sphingolipid metabolism is important because of their limited transbilayer and inter-membrane movement. For instance, glycosylceramide synthase converts de novo synthesized ceramide to glycosylceramide, but it is neither a general attenuator of ceramide accumulation at the plasma membrane, nor of the apoptotic process. Synthetic alkyl-lysophospholipids modulate membrane-lipid composition and, therefore, apoptosis sensitivity.